Commodity Outlook 2003: U.S. and Florida Ornamental Plant Markets - Alan W. Hodges; John J. Haydu (EDIS, 2003)
This paper will briefly review trends in ornamental plant production, consumption, and trade for the United States and Florida, and will also consider a study of the economic impacts of the Florida horticulture industry. This is EDIS document FE374, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published February 2003.